Translating French Drama for English Audiences: Adolphe Belot’s L’Article 47 - Barbara T. Cooper (Cahiers Victoriens et Edouardiens)
‘The extraordinary mess that two practised English writers, Messrs. [William Gorman] Wills and Frank Marshall, have made of M. [Adolphe] Belot’s L’Article 47, which they have turned into Cora, now being played at the Globe, gives a fresh proof that it is bad policy for English managers to rely upon a system of borrowing from the French stage’. So reads the opening sentence of the anonymous review published in The Saturday Review of Politics, Literature, Science and Art (Mar 3, 1877). Invoked by an American woman of colour abandoned by the French lover who had promised to marry her upon their arrival in France, the French law mentioned in the play’s original title serves to complicate a story of passions and punishment that takes place over a period of years. How was Cora received by English critics and audiences for whom French legal and dramatic codes were dissimilar from and at times at odds with their own national standards and expectations? What, if anything, can we learn about English cultural and racial stereotypes from the reviews of this sensational drama? These are some of the questions this essay will seek to answer.